An In Situ Fabricated Graphene/Bipolar Polymer Hybrid Material Delivers Ultralong Cycle Life over 15 000 Cycles as a High‐Performance Electrode Material. Issue 16 (9th March 2023) - Zhao, Yang; Xu, Nuo; Ni, Minghan; Wang, Ziyuan; Zhu, Jie; Liu, Jie; Zhao, Ruiqi; Zhang, Hongtao; Ma, Yanfeng; Li, Chenxi; Chen, Yongsheng
Abstract: Organic electrode materials are promising for the future energy storage systems owing to their tunable structures, abundant resources, and environmental friendliness. Many advanced lithium‐ion batteries with organic electrodes have been developed and show excellent performance. However, developing organic materials with overall superior performance still faces great challenges, such as low capacity, poor stability, inferior conductivity, and low utilization of active sites. To address these issues, a bipolar polymer (Fc‐DAB) is designed and further polymerized in situ with three‐dimensional graphene (3DG), offering a hybrid material (Fc‐DAB@3DG) with a variety of merits. Fc‐DAB possesses stable polymer backbone and multiple redox‐active sites that can improve stability and capacity simultaneously. The embedded highly conductive 3DG network endows Fc‐DAB@3DG with stable conductive framework, large surface area, and porous morphology all together, so the fast diffusion of ions/electrons can be achieved, leading to high utilization of active sites and enhanced electrochemical performance. As a result, Fc‐DAB@3DG cathode delivers capacity of ≈260 mA h g −1 at 25 mA g −1, ultra‐long cycle life over 15 000 cycles at 2000 mA g −1 with retention of 99.999% per cycle, and remarkable rate performance. The quasi‐solid Li‐metal battery and full cell fabricated using this material also exhibit superior electrochemical performance. Abstract : A graphene/bipolar polymer hybrid material (Fc‐DAB@3DG) is in situ fabricated through a simple one‐step solvothermal method. The Fc‐DAB component provides high capacity and stability, while the 3D interconnected conductive graphene network endows Fc‐DAB@3DG with fast ions/electrons diffusion and thus improved rate performance. Therefore, combined together, the material exhibits simultaneously high capacity, ultralong cycle life, and superior rate performance.